Aktualisasi Tanggungjawab Sosial Masyarakat pada Kelu arga Miskin d i Perdesaan: Studi Kasus Desa Pedalaman di Kabupaten Bone - Bustang Bustang; Basita G Sugihen; Margono Slamet; Djoko Susanto (Jurnal Penyuluhan, 2009)
This research was intended to formulate the strategy to increase The Actuality and Social Responsibility to Poor Families at Rural Area. Survey were implemented among 57 selected samples, started Nopember 2006 until April 2007. Data was analyzed by using both correlation and path analysis. The results indicated that a number of respondent had a high social responsibility. The increasement of social responsibility and level of empowerment were influenced by implementation of good government of local organization, income, and formal education. This study suggests an alternative model of empowerment in order to social responsibility.